As we live, so we believe, so we worship together : A liturgical exploration into the causal interrelationships between lex orandi, lex credendi, lex (con) vivendi - Scott, Hilton (Stellenbosch Theological Journal, 2021)
The adage lex orandi, lex credendi, lex vivendi (or lex (con)vivendi) denotes causal interrelationships between worship, belief and life. Simply one affects the others as this adage forms the foundation of doctrine and/or a moral life. However, if there are true causal relationships between “as we worship” (lex orandi), “so we believe” (lex credendi), “so we live” (lex vivendi) then the adage can also be understood as: “as we live” (lex vivendi), “so we believe” (lex credendi), “so we worship” (lex orandi). This leads o the question: how does popular art and music in the lived experience (lex vivendi) influence/affect belief and therefore worship? In terms of promoting acceptance in the church this investigation begins by using two examples from popular music by Taylor Swift and two examples from British rapper Stormzy with the supposition that the artists intend to provoke a change in thinking that encourages an ethical acceptance of difference across society. This article is from a paper that was presented at the 2021 Societas Liturgica Conference hosted by University of Notre Dame.